Surgery after combination therapy with a tyrosine kinase inhibitor and anti-PD-1 antibody in sarcomatoid hepatocellular carcinoma: case report and literature review - Liang, Bin; Huang, Tao; Kuang, Shao-Lei; Xie, Guang-Yuan; Liu, Tian-Qi; Chen, Yuan-Yuan (Frontiers in Oncology, 2023)
Introduction Although surgery is the preferred treatment for sarcomatoid hepatocellular carcinoma (SHC), the prognosis remains considerably poor due to early postoperative recurrence and metastasis. Reports on surgery after combined treatment with a tyrosine kinase inhibitor and anti-programmed cell death (PD)-1 antibody are unavailable. Case presentation A 69-year-old male patient with SHC was admitted to our hospital for treatment of a liver tumor that was detected on ultrasonography. Abdominal computed tomography with triple-phase enhancement revealed a lesion in the right hepatic lobe that measured 86.0 mm × 75.0 mm × 71.0 mm. Biopsy revealed a pathological diagnosis of liver sarcoma or sarcomatoid carcinoma. The patient subsequently received transcatheter arterial chemo-embolization, as he did not consent to surgery. More than two months later, he received a combination of lenvatinib with camrelizumab, as computed tomography showed an increase in the lesion size (to 123.0 mm × 90.0 mm × 80.0 mm) and lateral growth posterior to the upper pole of the right kidney. Liver resection was performed after 6 months of systemic therapy; pathological examination confirmed a diagnosis of SHC and showed extensive necrosis of tumor cells. Combined treatment with lenvatinib and camrelizumab was continued for 6 months after surgery. The patient has survived for over 24 months after initial diagnosis and is currently tumor-free. Conclusion Combined systemic therapy with a tyrosine kinase inhibitor and anti-PD-1 antibody may represent a feasible treatment strategy for improving resectability in cases of unresectable SHC. The outcomes with this combination may also be explored in cases of resectable SHC that have a high-risk of recurrence; this may improve the therapeutic effect.